Soil Heavy Metal Accumulation and Ecological Risk in Mount Wuyi: Impacts of Vegetation Types and Pollution Sources - Feng Wu; Donghai Zhu; Tao Yang; Cong Mao; Wubiao Huang; Shuangshi Zhou; Yujing Yang (Land)
Soil heavy metal (HM) contamination has become a critical global environmental issue, predominantly caused by industrial and agricultural operations. This study focuses on Mount Wuyi, a UNESCO biodiversity hotspot and major tea production base, to examine vegetation-mediated soil HM accumulation under anthropogenic impacts. We analyzed nine HMs (Mn, Cu, Zn, Cd, Hg, As, Pb, Cr, Ni) across diverse vegetation types using geochemical indices and Positive Matrix Factorization (PMF) modeling. The findings revealed Mn and Zn were dominant elements, and Cr and Pb concentrations exceeded regional background values by 3.47 and 1.26 times, respectively. Cr, Cd, and Pb demonstrated significant pollution levels, while Cd and Hg posed the highest ecological risks. Vegetation type significantly influenced HM distribution patterns, with cultivated areas and shrublands (including tea gardens) accumulating higher concentrations of Cu, Cd, Pb, and Hg from agricultural and transportation sources. Notably, bamboo forests exhibited natural resistance to HM contamination. PMF analysis identified four primary pollution sources: urbanization (27.94%), transport–agriculture activities (21.40%), agricultural practices (12.98%), and atmospheric deposition (12.96%). These results underscore the need for implementing clean energy solutions, phytoremediation strategies, and tea-specific detoxification measures to maintain ecological security and agricultural sustainability in this ecologically significant region.